Pri-povest i padu u "Grad na brdu": intertekstualnost i žanr kao teorijski faktori književne kritike (Milton u Americi Pitera Akrojda) (Philologia, 2021)
Is Milton in America an outrageous farrago of half-chewn pastiche, or a daring novel in its own right? This paper examines the literary merits of Peter Ackroyd's much-reviled novel by exosing critical prejudices in order to probe the criteria of literary criticism which would take into account the text as well as the author and the reader. The basic premise is that the text establishes its meaning through structure (genre, style and disposition of parts), which then interacts with the reader's experiential input in order to draw out a particular interpretation. Accordingly, the reliable way to approach this novel would be to establish its genre (pseudobiographic dystopia) and disentangle its transtextual threads (revealing it is a mixture of parody and pastiche).